Psychometric evaluation of the behavioral intention to use blended learning scale for Nigerian university lecturers - Ahmad, Abdulhamid Sanusi; Mittu, Harish; Kumar, Dinesh; Sadiq, Aisha Bello (Journal of Education and Learning (EduLearn), 2026)
Universities in Nigeria are not an exception to the growing trend of blended learning (BL) as a promising approach to higher education. The purpose of this study is to create and assess the psychometric qualities of a behavioral intention to use blended learning (BIUBL) scale designed for university lecturers in Nigeria. Data were gathered from 368 lecturers representing federal, state, and private universities using a descriptive survey design. The scale items were refined and the scale’s underlying structure was evaluated through the use of exploratory factor analysis (EFA) in SPSS 22.0. The factor structure was then validated by confirmatory factor analysis (CFA) using AMOS 20.0. The scale’s reliability of 0.835 was obtained by using the Cronbach’s alpha coefficient, suggesting strong internal consistency. The results demonstrated the validity and reliability of the scale in gauging the behavioral intention of lecturers to employ BL in Nigerian university settings. In order to evaluate and encourage university lecturers to use BL practices, this scale can be a useful tool for researchers and educators globally. The process of the creation of the scale followed the established rules for a tool construction which could also assist researchers with guidedance. These would ultimately improve the standard of higher education delivery in Nigeria and beyond.